The golden age of pirates : an interactive history adventure - Temple, Bob (You choose books., 2008)
"Describes the people and events of the Golden Age of Piracy. The reader's choices reveal the historical details from the perspective of a pirate, a navy sailor, and a merchant ship crewmember"--Provided by publisher.